Cursos de Filosofia no Rio Grande do Sul: Memórias e interdisciplinaridade (Razão e Fé, 2024)
The research “Philosophy Courses in Rio Grande do Sul: Memories and Interdisciplinarity” aims to present a brief historical overview of the characteristics of more than a dozen Philosophy Courses that worked and others that have already been extinguished. What is the political-pedagogical project that can be inferred from the objectives of the Courses? It can be found, initially, by explaining the method of teaching the perspective of learning the method of philosophizing. Then, there is the incentive to philosophical research, that is, teaching by researching. In this sense, the curricular organization articulates a pedagogical strategy. Finally, the philosophical act of the courses is organically inserted in the public space. This makes Philosophy relevant in society.